2011
DOI: 10.1152/ajpheart.00240.2010
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene attenuates Gas6 and apoptosis in experimental aortic valve disease in renal failure

Abstract: failure is associated with aortic valve calcification. Using our rat model of uremiainduced reversible aortic valve calcification, we assessed the role of apoptosis and survival pathways in that disease. We also explored the effects of raloxifene, an estrogen receptor modulator, on valvular calcification. Gene array analysis was performed in aortic valves obtained from three groups of rats (n ϭ 7 rats/group): calcified valves obtained from rats fed with uremic diet, valves after calcification resolution follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…As shown in Supplement Figure 1, neonatal cardiac fibroblasts from WT hearts did not increase FGF23 mRNA in response to high-phosphate medium supplemented either with rS100A12 (1ug/ml) or control BSA cultured for up to 20 days. As expected, genes important for the regulation of mineralization including osteocalcin (BGLAP), osteopontin (OPN) and Matrix gla protein (MGP), previously found at increased levels in calcific aortic valves of uremic animal models 29, 30 , increased in response to high-phosphate calcification medium. While rS100A12 did not alter expression of FGF23, rS100A12 reduced significantly gene expression of osteopontin by 20% to 40% (Supplement Figure 1C).…”
Section: Resultssupporting
confidence: 75%
“…As shown in Supplement Figure 1, neonatal cardiac fibroblasts from WT hearts did not increase FGF23 mRNA in response to high-phosphate medium supplemented either with rS100A12 (1ug/ml) or control BSA cultured for up to 20 days. As expected, genes important for the regulation of mineralization including osteocalcin (BGLAP), osteopontin (OPN) and Matrix gla protein (MGP), previously found at increased levels in calcific aortic valves of uremic animal models 29, 30 , increased in response to high-phosphate calcification medium. While rS100A12 did not alter expression of FGF23, rS100A12 reduced significantly gene expression of osteopontin by 20% to 40% (Supplement Figure 1C).…”
Section: Resultssupporting
confidence: 75%
“…RAL has certain effects on cardiovascular diseases, and previous studies revealed that RAL and other SERMs improve the function of vascular endothelial cells [19, 20], dilate the coronary artery [8, 21], and regulate blood fat [22]. However, only a few reports on basic and clinical studies of the effect of RAL on valvular heart disease have been published [23]. Based on the above discussion and description of many literatures, we found that the microsomal antiestrogen-binding site (AEBS) is a high-affinity membranous binding site for the antitumor drug RAL that selectively binds diphenylmethane derivatives of RAL such as PBPE (N-pyrrolidino-4-(phenylmethyphenoxyl)-ethanamine, HCl) and mediates their antiproliferative properties [2426].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying renal IRI are associated with the initiation of oxidative stress and inflammation, which are regulated by the growth arrest-specific 6 (Gas6) and its receptors Tyro3, Axl and MerTK, among which Gas6 exerts its anti-inflammatory effects mainly through Axl [4]. In acute stage, Gas6/Axl plays protective roles after IRI in multiple organs, including kidney, heart and liver [5].…”
Section: Introductionmentioning
confidence: 99%